Stan zdrowotny a zróżnicowanie genetyczne wybranych drzewostanów świerkowych na terenie RDLP w Krośnie - Gutkowska, Justyna; Borys, Małgorzata; Nowakowska, Justyna; Oszako, Tomasz; Tereba, Anna; Tkaczyk, Miłosz (Leśne Prace Badawcze, 2017)
The study was conducted in 2015 in six spruce stands situated in different forest districts administratively belonging to the Regional Directorate of Forests State in Krosno. Each spruce population was represented by 30 trees and assessed in terms of their current health status. Genetic analyses were performed based on shoot samples from each tree using nine nuclear DNA markers and one mitochondrial DNA marker (nad1). The health status of the trees was described according to the classification developed by Szczepkowski and Tarasiuk (2005) and the correlation between health classes and the level of genetic variability was computed with STATISTICA (α = 0.05). Nuclear DNA analyses revealed a low level of genetic variability among spruce populations (only 3% of the total genetic variation (FST = 0.028) and a high variability within populations (97%). The total heterozygosity in all stands (HT) was calculated as 0.646. Based on UPGMA analysis, the most genetically similar populations are spruce stands in the Bieszczady National Park and the Ustrzyki Dolne Forest District, which have the smallest genetic divergence of all populations (DN = 0.0165).Our analysis of the mitochondrial gene nad1 revealed the presence of six different haplotypes „a”, „a1”, „b”, „c”, „d” and „d1”. Comprising 56% of all haplotypes, „a” was the most common showing a predominant impact on spruce migration from the Carpathian area. The analysis based on mitochondrial markers (by Nei) revealed a heterozygosity of 0.525. Based on the observations of disease symptoms, 29% of the trees belong to health class 1,30% to class 2,28% to class 3 and class 4 contains 13% of trees. The comparison between health status and the level of genetic variation in the analyzed stands showed a positive correlation. Spruce stands with better health were also characterized by a greater degree of genetic variability. Since most of the investigated spruce populations shared the mitochondrial haplotype „a”, we have ascertained their Hercynian-Carpathian origin. Only one stand (Cisna) had a high frequency (43.3%) of the Nordic haplotype „c” suggesting that this provenance is derived from the Baltic post-glacial refugium of P. abies in Europe.